Efektivitas Pengelolaan Dana Desa oleh Pemerintah Desa Mekargalih Tahun 2023 - Mas Rasmini; Rosiana Alia Ahsan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to describe the effectiveness of village fund management in 2023 in Mekargalih Village based on indicators of goal achievement, integration, and adaptation as stated by Duncan in Steers (2003). The method used in this research is a qualitative method with the research object “Village Fund Management”. This research collected primary and secondary data obtained through semi-structured interviews, non-participant observation, literature study, and documentation study. The results showed that the Village Government was able to achieve the goals and objectives of using village funds, implement the applicable legal basis, carry out socialization and consensus, manage village funds according to procedures, and optimize the use of facilities and infrastructure. However, the disbursement of village funds and village fund activities are generally implemented late. Furthermore, training activities are considered not to have a significant impact to the capacity building of village officials. In addition, village governments face challenges in managing village funds in the form of limited village apparatus capacity and low levels of village independence. Overall, the village government has fulfilled most of the effectiveness indicators. Thus, it can be concluded that village fund management has been carried out effectively by the Mekargalih Village Government, but there are aspects that need to be improved to increase the effectiveness of village fund management in the future.